Drivers for Local Economic Development in South African Municipalities - Parker, Gail, Denise (My University, 2021)
Local economic development (LED) within municipalities in South Africa has been viewed as a failing project by many commentators, practitioners and scholars. One of the areas attributed as a causal factor for distrust on efforts related to local economic development is lack of clarity on foundational dynamics and drivers of LED. This study used interpretivist approaches to analyze key theoretical frameworks that provide explanations for challenges related to articulation of drivers for LED. As a theoretical paper authors established rigor through mapping theories to building blocks of a theoretical argument being the what, when, how and why. The central argument of this paper is that while the potential of LED strategies is not disputed and the economic value of land is , the implementation of such strategies does not assist in achieving the intended objectives of poverty alleviation and economic development. The study concluded that while local municipalities are mandated by the Constitution to “promote social and economic development”, they will not be able to do this without clear policy guidance; institutional capacity-building; inter-sectoral collaboration; political ‘champions’ to drive the process; and real empowerment of the beneficiaries whom the projects is supposed to assist. Key Words : Local economic development. Theoretical framework, Commonage, Business development, Black economic empowerment,
Keywords: Black economic empowerment; Business development; Commonage; Local economic development; Theoretical framework